1993
DOI: 10.1143/jjap.32.2613
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Amorphous Silicon Using Tetrasilane

Abstract: Hydrogenated amorphous-silicon films have been deposited by the plasma-free chemical-vapor-deposition method using tetrasilane (Si4H10) at temperatures as low as 350°C. The film deposited at 350°C and 9 Torr had hydrogen content as high as 15 at.%, optical bandgap of 1.78 eV, logarithmic ratio of photoconductivity (at a light intensity of 100 mW/cm2 under AM1 conditions) to dark conductivity of 3.2, activation energy of 0.78 eV and the Urbach tail slope as small as 56 meV. Thin-film transistors have been fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The experimental rate of particle growth d(r)/dt (where r is the particle radius) obtained from Figure 5 for (when disilane and t ϭ 0.1 s trisilane have the concentrations close to maximal) was compared with W evaluated from (3). We also took into account that under deposition from trisilane the rate of silicon layer growth is approximately two times higher than under deposition from disilane [46,53]. For the estimation showed that neous decomposition of silane and disilane are also the same and equals to Ͻ 0.5%.…”
Section: On Heterogeneous Decomposition Of Silane Disilane and Trismentioning
confidence: 99%
“…The experimental rate of particle growth d(r)/dt (where r is the particle radius) obtained from Figure 5 for (when disilane and t ϭ 0.1 s trisilane have the concentrations close to maximal) was compared with W evaluated from (3). We also took into account that under deposition from trisilane the rate of silicon layer growth is approximately two times higher than under deposition from disilane [46,53]. For the estimation showed that neous decomposition of silane and disilane are also the same and equals to Ͻ 0.5%.…”
Section: On Heterogeneous Decomposition Of Silane Disilane and Trismentioning
confidence: 99%
“…Complete desorption of hydrogen from the formed, presumably very unstable, compounds up to monohydride species will indeed result in a surface with the same amount of active Si-H sites for all three silanes at the beginning of each pulse. However, this need not necessarily be true, as can be inferred from literature on plasma-free CVD growth of hydrogenated amorphous silicon layers [28]. These layers were grown in the same temperature region in which the TAP experiments have been performed.…”
Section: Adsorption Of Silanes At Low Temperaturesmentioning
confidence: 99%
“…Alternatively, using higher order silanes, via CVD and PECVD resulted in incremental benefits to deposition temperature, rate and efficiency at the lab-scale. This approach has not yet been scaled to manufacturing levels, possibly due to the inconsistency in silane vaporization [3][4][5][6][7][8]. For an example, Chung et al, studied Si film deposition using neopentasilane (NPS) via lowpressure CVD, and found enhanced growth rates [4].…”
Section: Introductionmentioning
confidence: 99%